1956
DOI: 10.2337/diab.5.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Extracts in The Treatment of Diabetes Mellitus

Abstract: Since the year 1889, when von Mering and Minkowski produced severe and fatal diabetes by total removal of the pancreas in dogs, many investigators have endeavoured to obtain some beneficial effect in diabetes mellitus, either by feeding pancreas, or by administration of pancreatic extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
160
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(184 citation statements)
references
References 1 publication
(1 reference statement)
0
160
0
7
Order By: Relevance
“…With the discovery of extraction and administration of insulin in type 1 diabetes patients by Banting et al [10] in 1922, the overall quality of life improved for diabetes patients and there has been a decrease in morbidity and mortality. This was a novel idea and lifesaving discovery at that time, but the idea and initial attempts of islet transplantation from pancreatic tissue precluded it by 30 years.…”
Section: Islet Transplantation Historymentioning
confidence: 98%
See 1 more Smart Citation
“…With the discovery of extraction and administration of insulin in type 1 diabetes patients by Banting et al [10] in 1922, the overall quality of life improved for diabetes patients and there has been a decrease in morbidity and mortality. This was a novel idea and lifesaving discovery at that time, but the idea and initial attempts of islet transplantation from pancreatic tissue precluded it by 30 years.…”
Section: Islet Transplantation Historymentioning
confidence: 98%
“…Autologous canine pancreatic tissue graft [11] 1894 Xenotransplantation of pancreatic tissue to a ketoacidotic child [12] 1922 Discovery of insulin [10] 1989…”
Section: Disclosurementioning
confidence: 99%
“…Initially, von Mering and Minkowski (1889) reported that the removal of the pancreas produced a diabetic phenotype; it was subsequently found that crude pancreatic extracts produced moderate reductions in glycosuria (Piper, Allen, & Murlin, 1923). Then, in their ground-breaking work, Banting and Best (Banting, Best, Collip, Campbell, & Fletcher, 1922) demonstrated that insulin, isolated from pancreatic islets, could provide successful clinical treatment of type-1 diabetes. Insulin, purified from animal sources, rapidly became commercially available for the treatment of insulin-deficient (type-1) diabetes mellitus (Swann, 1986).…”
Section: Insulin Synthesis Secretion and Actionmentioning
confidence: 99%
“…The establishment of functional genomic technologies in therapeutics has addressed questions concerning the tissue specificity of the protein of interest as well as the level of protein(s) under normal and diseased states (1). One of the first and best examples of metabolic diseases efficiently treated with a protein therapeutic (PT) was the juvenille diabetes mellitus in 1922 (2). Recombinant DNA technology permitted the expression of human insulin gene in Escherichia coli (E. coli) bacteria cells (3).…”
Section: Introductionmentioning
confidence: 99%